Concordance between youth and caregiver report of eating disorder psychopathology: Development and psychometric properties of the Eating Disorder‐15 for Parents/Caregivers (ED‐15‐P). Issue 7 (22nd May 2021) - Accurso, Erin C.; Waller, Glenn
Abstract: Objective: Outcome measurement in youth with eating disorders relies heavily on self‐report, which is problematic in a population that may deny or minimize symptoms. Caregiver‐report measures are lacking. This study examined the psychometric and clinical properties of a newly‐developed measure designed to assess short‐term change in eating disorder symptomatology as observed by caregivers—the Eating Disorder‐15 for Parents/Caregivers (ED‐15‐P). Method: At initial presentation to an outpatient eating disorders assessment, 206 families (primary caregiver and their child up to 18 years old) completed psychological measures. Results: The ED‐15‐P demonstrated excellent reliability, preliminary evidence of discriminant and concurrent validity, and good sensitivity to change early in treatment (first 8 weeks). Agreement between primary caregivers and children on eating disorder psychopathology was moderate, while agreement between pairs of caregivers was relatively strong. Level of agreement varied across behaviors and informants, with poorer caregiver‐child agreement on dieting and driven exercise. Discussion: Agreement was stronger within caregiver pairs than caregiver‐child pairs, indicating that caregivers and their children have related but unique perspectives on eating disorder symptoms, highlighting the importance of multi‐informant assessment. The ED‐15‐P complements a parallel youth report measure to more comprehensively assess eating disorder psychopathology, with high utility for measuring change over time.